Elaboración del diagnóstico del grado de madurez en gestión de portafolio de las organizaciones del grupo de interés de PMO de Bogotá (2016)
This research aims to diagnose the portfolio maturity level of the organizations among PMO interest group in Bogotá, Colombia. For this, the authors created de Portfolio Maturity Model MMGPf which was developed from the information recollected from standards for portfolio management and from portfolio, programs and project maturity models, aiming to obtain a model that is adapted to reality and need of organizations evaluated. The research is exploratory, qualitative and action-research designed. The maturity model developed consists of 5 levels of maturity, consisting of three pillars (Strategic Planning, Portfolio Management Areas of Knowledge and Organizational Enablers), which are applied through an interview of 15 open-ended questions and a questionnaire of 110 closed-ended questions with five answer choices.